BIOMETRIC PARAMETERS OF PISTACHIO SEEDLINGS GROWN ON DIFFERENT SUBSTRATES - Hamzaev Abdushukur Khudoykulovich; Inomova Munira Murotjоn qizi (Journals Park Publishing, 2024)
The size of the container and the content of the substrate are important factors for growing quality and standard seedlings in a closed root system (container). The quality of the grown seedling, resistance to diseases and pests depends on the quality of the soil substrate. A rich composition of the substrate for growing plants with a closed root system ensures intensive growth of seedlings. In addition, many factors directly affect the successful growth of plants in the closed root system, including air temperature, irrigation regime, mineral nutrients, soil and relative humidity.
Keywords: Pistachio, substrate, germination, biometric, growing season, height, diameter, variant, control, nutrients, seeds, soil.